Navigating Bureaucratic Pressures and Preserving Islamic Pedagogy: Institutional Strategies of Mu’allimin Pesantren - Saifudin Asrori; Muhammad Isma’il; Ahmad Shabbir (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
This article examines how cadre based Mu’allimin pesantren in Indonesia strategically navigate the tension between preserving Islamic identity and adapting to bureaucratic educational reforms. Drawing on neo-institutional theory and Bourdieu’s concept of habitus, it employs a qualitative multi-case approach to analyse how four pesantren enact institutional reproduction through curricular hybridization, cultural filtering, leadership hybridity, and market-responsive adaptation. The findings reveal how these institutions engage in institutional work—not as passive actors but as agents of negotiated change—balancing symbolic compliance with internal continuity. By conceptualizing resilience as embedded, adaptive, and symbolic labour, this study advances institutional theory by highlighting how religious organizations sustain legitimacy and distinctiveness amid state-driven standardization.